Nitella (Streptophyta, Characeae) from southern Brazil - Bueno, Norma Catarina; Prado, João Fernando; Meurer, Thamis; Bicudo, Carlos Eduardo de Mattos (Iheringia, Série Botânica., 2016)
In this study, we analyzed 100 samples of Nitella C. Agardh emend. A. Braun emend. Leonhard from four diff erent Herbaria (ICN, SP, UNOP-Algae and UPCB), which represented 66 diff erent locations from the southern region of Brazil. Twenty-two species of Nitella (Streptophyta, Characeae) were described and illustrated from the states Paraná, Santa Catarina and Rio Grande do Sul, eight of which are new records for the region. Considering the three states studied, three species were new records for Paraná [N. flagellifera J. Groves & G.O. Allen, N. mucronata (A. Braun) Miquel in H.C. Hall and N. opaca (C. Agardh ex Bruzelius) C. Agardh], three species for Santa Catarina (N. blankinshipii T.F. Allen, N. flagellifera J. Groves & G.O. Allen and N. subglomerata A. Braun) and another two for Rio Grande do Sul [N. flexilis (L.) C. Agardh and N. microcarpa A. Braun].